Dietary Antioxidants and Brain Health: Focus on Cognitive and Affective Disorders - Justyna Godos; Giuseppe Grosso (MDPI AG, 2021)
Today's society faces major global challenges, including the continuously increasing prevalence of mental disorders and neurodegenerative diseases, with different risk factors contributing to the trend [...]